Nghiên cứu chế tạo vật liệu cao su nanocompozit trên cơ sở blend cao su thiên nhiên với cao su cloropren gia cường ống nano cacbon bằng phương pháp bán khô - Vân, Chu Anh; Hiệp, Ngô Quang; Oanh, Hồ Thị; Hải, Lương Như; Tùng, Ngô Trịnh; Kháng, Đỗ Quang (Vietnam Journal of Chemistry, 2016)
The rubber nanocomposites based on NR/CR blends and CNT were prepared by the two methods. By the first method, the surfactant was used for dispersion of CNT in NR latex then NR/CNT mixtures, CR and other fillers were mixed using a mixer. By the second method CNT and the rubber components were separately dispersed in toluene and then mixed together. After that the rubber/CNT mixture and other fillers were further mixed using a mixer. The rubber nanocomposites were vulcanized at 145 oC for 20 min. The results reveal that CNT were well dispersed in rubber blend by FE-SEM images. The optimal CNT content for reinforcement of NR/CR blend was 3 % and the mechanical properties of the NR/CR blend were significantly improved. The tensile strength, the thermal decomposition temperature increased about 50.3 % and 8 oC, respectively. The electrical percolation threshold of the materials was reached at CNT content of 4 % with the electrical conductivity of 10-5 S/cm.